The Effect of Religiosity and Service Quality on Job Satisfaction: A Case Study of MSME Employees - Amri, Whan Augustin Ainul; Asbari, Masduki; Gazali, Gazali; Novitasari, Dewiana; PURWANTO, AGUS (International Journal of Social and Management Studies, 2021)
This study aims to analyze the effect of religiosity and service quality on job satisfaction in micro, small and medium enterprise (MSME) industry employees by taking a sample of 120 employees from ten MSME industries in Indonesia. The data collection method used a questionnaire. The analysis method uses Structural Equation Modeling (SEM), Smart PLS v.3.0. The results showed that religiosity had a positive and significant effect on service quality. Religiosity has a positive and significant effect on employee job satisfaction, and service quality has a positive and significant effect on employee job satisfaction. Research results can be used as a basis for improving and maintaining employee job satisfaction in MSME industries through increasing religiosity and service quality of company employees.